Texture enhancement of salted Alaska pollock (Theragra chalcogramma) roe using microbial transglutaminase. (30th August 2019) - Chen, Chaoping; Takahashi, Kigen; Geonzon, Lester; Okazaki, Emiko; Osako, Kazufumi
Highlights: ETGase activity in Alaska pollock roe decreased during frozen storage. Mechanical properties of the salted Alaska pollock roe was improved using MTGase. Adding 0.5% MTGase was the optimum to enhance the texture of the salted roe. MTGase can be used to improve the texture of aquatic processed food at 5 °C. Abstract: The aim of our study was to improve the texture quality of salted Alaska pollock ( Theragra chalcogramma ) roe product using microbial transglutaminase (MTGase). Thus, the effect of 0–1.0% MTGase on the physical properties of the salted roe was assessed. Endogenous TGase activity in the roe, which contributes to improving its texture, decreased at −20 °C during frozen storage. Mechanical properties of the salted roe, such as roe firmness and egg breaking strength, were improved using MTGase, the optimum concentration of which was 0.5%. Protein polymerizations using SDS-PAGE and decreasing of protein solubilities in SDS–urea solution were observed in the salted roe with MTGase. Therefore, the texture of salted Alaska pollock roe can be significantly enhanced by adding 0.5% MTGase because of catalyzing protein crosslinking. Additionally, this study most likely indicates that MTGase can be used to improve the texture of aquatic processed foods at low temperatures, especially 5 °C.